Livestock and Water Resources: A Comparative Study of Water Footprint in Different Farming Systems - Arrien, Macarena (2025)
Livestock production systems are major consumers of freshwater, potentiallycompromising the sustainability of water resources at production sites. The water footprint(WF) quantifies the water consumed and polluted by a product or service. The aim ofthis study was to evaluate the WF of steer production from the cradle to the farm gate inrepresentative intensive, extensive, and mixed farms located in the southeast of BuenosAires province, Argentina. The WF to produce a live steer varied between 4247 and5912 m3/animal. The extensive system contains the highest green WF but is also themost sustainable compared to industrial and mixed productions since it does not have anassociated pollutant load or blue water. This work is the first approach to calculating theWF of live steers in Argentina carried out with local and detailed data and focuses on greyWF related to nitrogen leaching from effluents in intensive systems, showing that the blueand grey footprints increase as production intensifies. The information may be relevant forconsumers and producers to make more informed decisions. Furthermore, it is essentialfor governments to promote sustainable practices in livestock farming, recognizing thedependence on water resources both domestically and throughout international supplychains, in order to assess their environmental policies and ensure national food security.